Composite positive electrode active material, positive electrode and lithium battery each containing the same, and preparation method thereof
By using composite positive electrode active materials in lithium batteries, using the nickel-lithium transition metal oxide and phosphorus components with multi-layer structure, the life and thermal stability of Ni materials are solved, and the performance and life of lithium batteries are significantly improved.
Patent Information
- Application Number
- CN201910962058.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-10-24
- Filing Date
- 2019-10-11
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-01-23
AI Technical Summary
Ni-based positive electrode active material has problems with insufficient life characteristics and thermal stability in lithium batteries, resulting in deterioration of battery performance.
Using a composite positive electrode active material, the material consists of a first lithium transition metal oxide containing nickel and a multi-layer structure, the first layer contains a specific metal component such as Co or Mg, and the second layer contains phosphorus, and a stable structure is formed by heat treatment to inhibit it. Side reactions.
It effectively suppresses the deterioration of battery performance, improves the circulation characteristics and thermal stability of lithium batteries, and extends the battery life.
Smart Images

Figure CN111092197B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2018-0127694 filed in the Korean Intellectual Property Office on October 24, 2018, the contents of which are incorporated herein by reference in their entirety. Technical Field
[0003] The present disclosure relates to a composite cathode active material, a cathode and a lithium battery each including the same, and a method for preparing the composite cathode active material. Background Art
[0004] With the development of various compact high-performance devices, there is an increasing demand for lithium batteries that have high energy density in addition to compactness and high performance. That is, high-capacity lithium batteries are becoming more and more important.
[0005] In order to realize a lithium battery satisfying such requirements, research on a positive electrode active material having an improved capacity has been conducted.
[0006] Ni-based cathode active materials are attractive because they can have high capacity and low cost, but their lifespan characteristics and thermal stability need to be improved.
[0007] Therefore, there is a need to develop a method for preventing battery performance from deteriorating when using Ni-based positive electrode active materials. Summary of the invention
[0008] Provided is a composite cathode active material capable of preventing degradation of battery performance by suppressing a side reaction of the composite cathode active material.
[0009] A positive electrode including the composite positive electrode active material is provided.
[0010] A lithium battery including the positive electrode is provided.
[0011] A method for preparing the composite positive electrode active material is provided.
[0012] Additional aspects will be set forth in part in the description which follows and, in part, will be apparent from the description, or may be learned by practice of the presented embodiments.
[0013] According to an aspect of one embodiment, a composite positive electrode active material includes: a core including a plurality of primary particles; and a shell formed on the core, wherein the primary particles include a first lithium transition metal oxide including nickel, the shell includes a first layer and a second layer on the first layer, the first layer includes a first component including a first metal, the second layer includes a second component including phosphorus, and the first metal includes at least one metal other than nickel belonging to any of Groups 2 to 5 and Groups 7 to 15 of the periodic table.
[0014] According to an aspect of another embodiment, a positive electrode includes the composite positive electrode active material.
[0015] According to an aspect of another embodiment, a lithium battery includes: the positive electrode; a negative electrode; and an electrolyte between the positive electrode and the negative electrode.
[0016] According to an aspect of another embodiment, a method for preparing a composite positive electrode active material includes: providing a first lithium transition metal oxide; mixing the first lithium transition metal oxide with a first metal precursor to prepare a first composition; mixing the first composition with a phosphorus precursor to prepare a second composition; drying the second composition; and heat treating the dried second composition at a temperature of about 400°C to about 1000°C in an oxidizing atmosphere to prepare the composite positive electrode active material. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] This patent or application file contains at least one drawing executed in color. Copies of this patent or patent application publication with color drawing(s) will be provided by the Office upon request and payment of the necessary fee.
[0018] These and / or other aspects will become apparent and more readily appreciated from the following description of the embodiments considered in conjunction with the accompanying drawings, in which:
[0019] Figure 1A A schematic diagram partially illustrating the internal structure of a composite positive electrode active material according to an embodiment;
[0020] Figure 1B is a schematic cross-sectional view of a composite positive electrode active material according to an embodiment;
[0021] Figure 2A and 2B Each is a graph of intensity (arbitrary unit, au) versus diffraction angle (degree, 2θ), which respectively shows the results of X-ray diffraction (XRD) analysis of the composite positive active materials prepared according to Reference Example 1 and Example 1;
[0022] Figure 3AA high angle annular dark field (HAADF) scanning transmission electron microscopy (STEM) image of a cross section of a composite positive electrode active material prepared according to Reference Example 1;
[0023] Figure 3B and 3C was prepared according to Reference Example 1 and shown in Figure 3A Energy dispersive X-ray spectroscopy (EDS) image of a cross section of a composite cathode active material;
[0024] Figure 4A is a HAADF STEM image of a cross section of a composite positive electrode active material prepared according to Example 1;
[0025] Figures 4B-4D was prepared according to Example 1 and shown in Figure 4A EDS image of the cross section of the composite cathode active material;
[0026] Figure 5 is a graph of heat flow (milliwatt, mW) versus temperature (° C.), which shows differential scanning calorimetry (DSC) thermograms of the composite positive active materials prepared according to Example 1 and Comparative Example 3; and
[0027] Figure 6 is a schematic diagram of a lithium battery according to an embodiment. DETAILED DESCRIPTION
[0028] Embodiments will now be described in detail, examples of which are shown in the accompanying drawings, wherein the same reference numerals represent the same elements throughout. In this regard, the present embodiment may have different forms and should not be construed as being limited to the description set forth herein. Therefore, the embodiments are described below only by reference to the accompanying drawings to illustrate aspects. As used herein, the term "and / or" includes any and all combinations of one or more of the relevant listed items. Expressions such as "at least one (individual) of..." modify the entire list of elements when before or after a list of elements, rather than modifying the individual elements of the list.
[0029] Since the present invention allows for multiple changes and many embodiments, specific embodiments are shown in the drawings and described in detail in the written description. However, it is not intended that the present disclosure be limited to the specific forms disclosed, but on the contrary, the present disclosure will cover all modifications, equivalents and substitutes falling within the spirit and scope of the present disclosure.
[0030] The terms used in this specification are only used to describe specific embodiments, and are not intended to limit the present disclosure. The expressions used in the singular include plural expressions, unless they have significantly different meanings in the context. Hereinafter, it will be understood that terms such as "including (comprising)" or "having" are intended to represent the presence of features, quantities, operations, components, parts, elements, materials or combinations thereof disclosed in the specification, without intending to exclude the possibility that one or more other features, quantities, operations, components, parts, elements, materials or combinations thereof may be present or may be added. As used herein, " / " may be interpreted as "and" or "or".
[0031] In the drawings, the thickness of layers and regions may be enlarged or reduced for clarity. Throughout the specification, the same reference numerals represent the same elements. Throughout the specification, it will be understood that when an element such as a layer, region or plate is referred to as "on" another element, it may be directly on the other element, or there may be an intermediate element therebetween. It will be understood that although the terms first, second, etc. may be used herein to describe a variety of components (assemblies), these components (assemblies) should not be limited by these terms. These terms are only used to distinguish one component (assembly) from another.
[0032] It will be understood that although the terms "first", "second", "third", etc. may be used herein to describe a variety of elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings herein, the "first element", "component", "region", "layer" or "part" discussed below may be referred to as a second element, component, region, layer or part.
[0033] The terms used herein are only used for the purpose of describing specific embodiments and are not intended to be restrictive. As used herein, the singular forms "a (individual) (indefinite article, a, an)" and "said (the)" are intended to include plural forms, including "at least one (individual)", unless the content clearly stipulates otherwise. "At least one (individual)" is not interpreted as limiting "a (individual)". "Or" means "and / or". As used herein, the term "and / or" includes any and all combinations of one or more of the relevant listed items. It will be further understood that the terms "include" and / or "comprising" when used in this specification indicate the presence of the described features, regions, wholes, steps, operations, elements and / or components, without excluding the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components and / or their collections.
[0034] For ease of description, spatially relative terms such as "under", "below", "lower", "above", "upper", etc. may be used herein to describe the relationship of one element or feature to another element or feature as shown in the figure. It will be understood that in addition to the orientation depicted in the figure, the spatially relative terms are also intended to include different orientations of the device in use or operation. For example, if the device in the figure is flipped, the element described as "under" or "below" another element or feature will be oriented "above" another element or feature. Therefore, the exemplary term "under" may include both above and below. The device can be oriented in other ways (rotated 90 degrees or in other orientations), and the spatially relative descriptors used in this article are interpreted accordingly.
[0035] As used herein, "about" or "approximately" is inclusive of the stated value and means within an acceptable range of deviation for the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations of the stated value, or within ±30%, 20%, 10%, or 5%.
[0036] Unless otherwise defined, all terms (including technical and scientific terms) used in this article have the same meaning as commonly understood by ordinary technicians in the field to which the present disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as their meanings consistent with their meanings in the context of the present disclosure and the relevant art, and will not be interpreted in an idealized or excessive formal sense unless clearly defined in this article.
[0037] Exemplary embodiments are described herein with reference to schematically illustrated cross-sectional views as idealized embodiments. As such, deviations from the illustrated shapes as a result of, for example, manufacturing techniques and / or tolerances are to be expected. Therefore, the embodiments described herein should not be construed as being limited to the specific shapes of the regions as illustrated herein, but rather include deviations in shape resulting from, for example, manufacturing. For example, a region illustrated or described as flat may typically have rough and / or non-linear features. Moreover, illustrated sharp corners may be rounded. Therefore, the regions illustrated in the figures are schematic in nature and their shapes are not intended to illustrate the precise shape of the regions and are not intended to limit the scope of the claims.
[0038] "Transition metal" as defined herein refers to an element from Groups 3 to 12 of the Periodic Table of Elements.
[0039] Hereinafter, a composite cathode active material, and a cathode and a lithium battery each including the same, and a method of preparing the composite active material will be described in more detail.
[0040] According to an embodiment, a composite positive electrode active material includes: a core including a plurality of primary particles; and a shell formed on the core, wherein each primary particle includes a nickel-based first lithium transition metal oxide including nickel (Ni), the shell having a first layer and a second layer located on the first layer, the first layer including a first component including a first metal, the second layer including a second component including phosphorus (P), the first metal including at least one metal other than nickel belonging to any of Groups 2 to 5 and Groups 7 to 15 of the periodic table.
[0041] Reference Figure 1A , the composite positive active material 300 includes: a core 100 having a plurality of primary particles 10; and a shell 200 formed on the core 100. The core 100 is a secondary particle including a plurality of primary particles 10. For example, the primary particles 10 are crystallites having the same crystal structure in the primary particles 10. The primary particles 10 include a first lithium transition metal oxide based on Ni containing nickel, and the shell 200 has a multilayer structure including a first layer (not shown) and a second layer (not shown) located on the first layer. The first layer includes a first component containing a first metal, and the second layer includes a second component containing phosphorus (P). The first metal includes at least one metal other than nickel belonging to any of Groups 2 to 5 and Groups 7 to 15 of the periodic table. The first lithium transition metal oxide based on Ni has a layered crystal structure.
[0042] Hereinafter, a theoretical basis for improved performance of a composite positive active material according to an embodiment will be described. This description is for the purpose of understanding the present disclosure and is not intended to limit the present disclosure.
[0043] The first layer including the first component containing the first metal is located on the core 100 of the composite positive active material 300, for example, for the purpose of stabilizing the surface of the core 100 and for the recovery of the performance of the active material deteriorated by washing the core 100 with water. Since the metal included in the core 100 is intermixed with the metal included in the first layer by the heat treatment performed during the process of preparing the first layer, the effect of stabilizing the surface structure of the core 100 and recovering the performance of the active material can be obtained. A second layer including a second component containing P is additionally formed on the first layer. The second layer serves as a protective layer for protecting the core and / or the first layer and suppressing its side reaction with the electrolyte solution. In addition, since the second layer including the second component containing P is additionally formed on the first layer, for example, Ni ions can be effectively suppressed from eluting from the core 100 to the electrolyte solution. Moreover, since the precursor of the second component reacts with the lithium remaining on the core 100 and / or the first layer during the process of forming the second layer, the amount of lithium remaining on the surface of the composite positive active material 300 is reduced. Therefore, for example, the side reaction (if any) and gas generation between the composite positive active material 300 and the electrolyte solution are effectively suppressed. In addition, since a stable artificial solid electrolyte interface (SEI) is formed by the reaction between the second layer and moisture or HF during the initial charge and discharge of the lithium battery, the generation of byproducts caused by the additional side reaction between the composite positive active material 300 and the HF or moisture remaining in the electrolyte solution is suppressed. Therefore, the surface of the composite positive active material 300 is stabilized. That is, since the second layer acts as a protective layer with lithium ion conductivity, the stability of the composite positive active material 300 is improved. In addition, since the second layer is polar and has improved wettability to the electrolyte solution, the interface resistance between the composite positive active material 300 and the electrolyte solution is reduced. Therefore, despite the addition of the second layer thereto, the internal resistance of the lithium battery including the composite positive active material 300 is maintained or reduced. As a result, the cycle characteristics and thermal stability of the lithium battery including the composite positive active material 300 are improved.
[0044] Among the transition metals included in the first lithium transition metal oxide included in the composite positive active material 300, the amount of Ni may be about 70 mol% (mol%) or more, about 71 mol% or more, about 75 mol% or more, about 80 mol% or more, about 85 mol% or more, about 90 mol% or more, about 93 mol% or more, about 95 mol% or more, or about 97 mol% or more, or about 71 mol% to about 99 mol%, about 75 mol% to about 98 mol%, or about 78 mol% to about 90 mol%, based on the total transition metal content of the first lithium transition metal oxide. When the amount of Ni included in the first lithium transition metal oxide is 70 mol% or more, a high capacity can be obtained. Therefore, a lithium battery providing a high capacity is achieved.
[0045] The first component included in the first layer has a first phase, and the second component included in the second layer has a second phase different from the first phase. The first phase and the second phase are different in crystal structure, composition, or both, for example.
[0046] For example, the first component includes at least one of the following phases: a phase having a layered crystal structure and a phase having a spinel crystal structure. For example, the first component includes a phase having a layered crystal structure belonging to the R-3m space group. For example, the first component includes a spinel crystal structure belonging to the Fd-3m space group. When the first component includes such a phase, the cycle characteristics and thermal stability of the lithium battery are further improved.
[0047] The first layer is formed on the primary particles constituting the core, and the concentration of the first metal included in the first layer is greater than the concentration of the first metal included in the primary particles. Figure 3B and 4B , the first layer is formed on the primary particles constituting the core, and the concentration of Co included in the first layer is greater than the concentration of Co included in the primary particles. Figure 3B and 4B , a greater Co concentration corresponds to a brighter color. For example, a concentration of the first metal per unit area of the first layer is greater than a concentration of the first metal per unit area of the primary particles.
[0048] In the composite positive electrode active material, for example, the thickness of the second layer of the shell is greater than the thickness of the first layer. Since the second layer has a thickness greater than that of the first layer, the elution of metal ions and the side reaction between the composite positive electrode active material and the electrolyte solution are more effectively suppressed. Therefore, despite the addition of the second layer having a thickness greater than that of the first layer, the lithium battery including the composite positive electrode active material 300 has improved cycle characteristics.
[0049] For example, the thickness of the first layer is 50 nanometers (nm) or less, 40nm or less, 30nm or less, 20nm or less, 10nm or less, or 5nm or less. For example, the thickness of the first layer may be about 1nm to about 50nm, about 1nm to about 40nm, about 1nm to about 30nm, about 1nm to about 20nm, about 1nm to about 10nm, or about 1nm to about 5nm, about 2nm to about 50nm, about 4nm to about 40nm, about 6nm to about 30nm, or about 8nm to about 20nm. When the first layer has a thickness within the above range, the cycle characteristics and thermal stability of the lithium battery are further improved. For example, the thickness of the second layer is about 500nm or less, about 400nm or less, about 300nm or less, about 200nm or less, about 100nm or less, or about 50nm or less. For example, the thickness of the second layer may be from about 10 nm to about 500 nm, from about 10 nm to about 400 nm, from about 10 nm to about 300 nm, from about 10 nm to about 200 nm, or from about 10 nm to about 100 nm, or from 20 nm to about 500 nm, from about 30 nm to about 400 nm, or from about 50 nm to about 300 nm. When the second layer has a thickness within the above range, the cycle characteristics and thermal stability of the lithium battery are further improved.
[0050] In the composite positive electrode active material, the thickness of the shell including the first layer and the second layer is, for example, about 550nm or less, about 450nm or less, about 350nm or less, about 250nm or less, about 150nm or less, or about 50nm or less. For example, the thickness of the shell may be about 10nm to about 550nm, about 10nm to about 450nm, about 10nm to about 350nm, about 10nm to about 250nm, about 10nm to about 150nm, or about 10nm to about 50nm, about 20nm to about 550nm, about 40nm to about 450nm, about 60nm to about 350nm, about 80nm to about 250nm, about 100nm to about 150nm. When the shell has a thickness within the above range, the cycle characteristics and thermal stability of the lithium battery are further improved.
[0051] In the composite positive electrode active material, the shell partially or completely covers the surface of the core. For example, the shell covers at least about 10%, at least about 20%, at least about 30%, at least about 40%, or at least about 50%, or about 10% to about 100%, about 20% to about 98%, or about 30% to about 90% of the entire surface of the core. The shell can be formed on the core in the form of discontinuous islands or as a continuous coating. Figures 4A-4D, for example, the shell is located on a plurality of primary particles exposed through a surface of the core.
[0052] For example, the first component is located on (eg, directly located on) the primary particles constituting the core and / or on the secondary particles corresponding to the core.
[0053] The first metal included in the first component may be, for example, at least one of Co, Mg, Zr, Al, Mn, Si, Pd, Ti, Sn, Ir, Pt, Ru, Ce, B, Nb, V, Fe, and Zn. When the first component includes such a first metal, the cycle characteristics and thermal stability of the lithium battery including the composite positive active material are further improved. When the first layer includes, for example, Co (which provides improved discharge capacity), the capacity reduction of the composite positive active material can be suppressed. When the first layer includes, for example, Mg, the structural stability of the composite positive active material is improved, thereby improving the life characteristics of the lithium battery including the composite positive active material. As used herein, "metals" such as first metals and second metals include metalloids such as Si and B.
[0054] In the composite positive electrode active material, the first component is, for example, a component including the first metal and oxygen, or a component including lithium, the first metal and oxygen. For example, the first component includes about 0 moles to about 3.3 moles of lithium per 1 mole of the first component, about 0.7 moles to about 3.3 moles of the first metal per 1 mole of the first component, and about 1.7 moles to about 4.3 moles of oxygen per 1 mole of the first component. For example, the first component includes about 0 moles to about 3.2 moles of lithium per 1 mole of the first component, about 0.8 moles to about 3.2 moles of the first metal per 1 mole of the first component, and about 1.8 moles to about 4.2 moles of oxygen per 1 mole of the first component. For example, the first component includes about 0 moles to about 3.1 moles of lithium per 1 mole of the first component, about 0.9 moles to about 3.1 moles of the first metal per 1 mole of the first component, and about 1.9 moles to about 4.1 moles of oxygen per 1 mole of the first component. When the first component includes a component within the above range, the cycle characteristics and thermal stability of the lithium battery including the composite positive electrode active material are further improved.
[0055] For example, the first component has a composition represented by Formula 1.
[0056] Formula 1
[0057] Li a M1 b O c
[0058] In Formula 1, M1 includes at least one of the following: Co, Mg, Zr, Al, Mn, Si, Pd, Ti, Sn, Ir, Pt, Ru, Ce, B, Nb, V, Fe, and Zn, 0 ≤ a ≤ 3.1, 0.9 ≤ b ≤ 3.1, and 1.9 ≤ c ≤ 4.1.
[0059] For example, the first component includes at least one of the following: Co 3 O 4 , MgO, Li x CoO 2 (0 < x ≤ 1.5), and Li 2 ZrO 3 .
[0060] In the composite cathode active material, the amount of the first component or the first metal included in the first layer is, for example, about 10 parts by weight or less, about 5 parts by weight or less, about 4 parts by weight or less, about 3 parts by weight or less, about 2 parts by weight or less, or about 1 part by weight or less, based on 100 parts by weight of the first lithium transition metal oxide. The amount of the first component or the first metal included in the first layer is, for example, about 0.01 parts by weight to about 10 parts by weight, about 0.05 parts by weight to about 5 parts by weight, about 0.1 parts by weight to about 4 parts by weight, about 0.1 parts by weight to about 3 parts by weight, about 0.1 parts by weight to about 2 parts by weight, or about 0.1 parts by weight to about 1 part by weight, based on 100 parts by weight of the first lithium transition metal oxide. When the first layer includes the first component or the first metal within the above range, the cycle characteristics and thermal stability of the lithium battery including the composite cathode active material are further improved.
[0061] In the composite positive electrode active material, the second component is, for example, a component including the first metal, phosphorus (P), and oxygen, or a component including lithium, the first metal, phosphorus (P), and oxygen. For example, the second component includes 0 to about 3.3 moles of lithium per 1 mole of the second component, about 0.7 to about 3.3 moles of the first metal per 1 mole of the second component, about 0.7 to about 2.3 moles of phosphorus per 1 mole of the second component, and about 3.7 to about 8.3 moles of oxygen per 1 mole of the second component. For example, the second component includes about 0 to about 3.2 moles of lithium per 1 mole of the second component, about 0.8 to about 3.2 moles of the first metal per 1 mole of the second component, about 0.8 to about 2.2 moles of phosphorus per 1 mole of the second component, and about 3.8 to about 8.2 moles of oxygen per 1 mole of the second component. For example, the second component includes about 0 to about 3.1 moles of lithium per 1 mole of the second component, about 0.9 to about 3.1 moles of the first metal per 1 mole of the second component, about 0.9 to about 2.1 moles of phosphorus per 1 mole of the second component, and about 3.6 to about 8.4 moles of oxygen per 1 mole of the second component. When the second component includes components within the above range, the cycle characteristics and thermal stability of the lithium battery including the composite positive active material are further improved. The second component includes, for example, a phosphate compound.
[0062] The second component has a composition represented by Formula 2 below.
[0063] Formula 2
[0064] Li a M2 b (PO 4 ) c
[0065] In Formula 2, M2 includes at least one of the following: Co, Mg, Zr, Al, Mn, Si, Pd, Ni, Ti, Sn, Mo, Ir, Pt, Ru, Ce, B, Nb, V, Fe, and Zn, 0≤a≤3.1, 0.9≤b≤3.1, and 0.9≤c≤2.1.
[0066] For example, the second component includes at least one of the following: Li 3 PO 4 、LiCoPO 4 , and Co 3 (PO 4 ) 2 .
[0067] In the composite positive electrode active material, the amount of the second component or phosphorus (P) included in the second layer is, for example, about 10 parts by weight or less, about 5 parts by weight or less, about 4 parts by weight or less, about 3 parts by weight or less, about 2 parts by weight or less, or about 1 part by weight or less, based on 100 parts by weight of the first lithium transition metal oxide. The amount of the second component or phosphorus (P) included in the second layer is, for example, about 0.01 parts by weight to about 10 parts by weight, about 0.05 parts by weight to about 5 parts by weight, about 0.1 parts by weight to about 4 parts by weight, about 0.1 parts by weight to about 3 parts by weight, about 0.1 parts by weight to about 2 parts by weight, or about 0.1 parts by weight to about 1 part by weight. When the second layer includes the second component or phosphorus (P) within the above range, the cycle characteristics and thermal stability of the lithium battery including the composite positive electrode active material are further improved.
[0068] The second component may be located on the primary particles constituting the core and / or on the secondary particles corresponding to the core. For example, the second layer is located on the first layer and selectively on the core. For example, a portion of the second layer is located on the surface of the core.
[0069] Reference Figure 1A and 1BIn the composite positive active material 300, the core 100 includes a grain boundary 20 between adjacent primary particles, each of which is located among the plurality of primary particles 10, and the grain boundary 20 includes a third component containing a second metal. Since the grain boundary 20 between the adjacent primary particles, each of which is located among the plurality of primary particles 10 constituting the core 100 of the composite positive active material 300, includes the third component, the lithium ion conductivity in the core 100 is increased, and the elution of Ni ions from the primary particles 10 in the core 100 to the electrolyte solution penetrating into the core 100 is suppressed. Moreover, the side reaction between the primary particles 10 and the electrolyte solution is suppressed in the core 100. Therefore, the cycle characteristics of the lithium battery including the composite positive active material 300 are improved. In addition, since the amount of lithium remaining on the surface of the plurality of primary particles 10 in the core 100 is reduced, the degradation of the composite positive active material 300 is suppressed and the gas generation is reduced, thereby improving the thermal stability of the lithium battery. Since the third component included in the grain boundary 20 between the adjacent primary particles 10 prevents the surface of the primary particles 10 from being damaged during the process of washing the composite positive electrode active material 300, the life characteristics of the lithium battery may not be impaired. Since the third component included in the grain boundary 20 between the adjacent primary particles 10 prevents cracks from occurring between the primary particles 10 by buffering the volume change of the primary particles 10 caused by charging and discharging, the mechanical strength of the composite positive electrode active material 300 is prevented from being reduced even after long-term use, thereby preventing the degradation of the lithium battery. In addition, since the lithium transition metal oxide included in the primary particles 10 is doped with the second metal included in the third component, the crystal structure of the lithium transition metal oxide is stabilized, and thus the cycle characteristics of the lithium battery including the composite positive electrode active material 300 are further improved.
[0070] For example, the third component included in the grain boundary 20 has a third phase that is different from the phase of the primary particle 10. The third phase may be different from the phase of the primary particle 10 in structure, composition, or both. The third phase has, for example, a monoclinic crystal structure. Since the third component has a monoclinic crystal structure, lithium ions can move two-dimensionally in the grain boundary 20 including the third component, and the lithium ion conductivity in the core 100 is increased, thereby improving the cycle characteristics. For example, the third component has a monoclinic crystal structure belonging to the C2 / m, C12 / c1, or C2 / c space group. Since the third component has a monoclinic crystal structure belonging to the C2 / m, C12 / c1, or C2 / c space group, the cycle characteristics and thermal stability of the lithium battery including the composite positive active material are further improved.
[0071] The second metal included in the third component is, for example, at least one of Zr, Al, Co, Mg, Mn, Si, Mo, Pd, Ti, Sn, Ir, Pt, Ru, Ce, B, Nb, V, Fe, and Zn. Since the third component includes the second metal, the charge and discharge characteristics of the lithium battery including the composite positive active material 300 are further improved.
[0072] In the composite positive electrode active material, the third component may include lithium, the second metal and oxygen. For example, the third component includes about 1.7 moles to about 2.3 moles of lithium per 1 mole of the third component, about 0.7 moles to about 1.3 moles of the second metal per 1 mole of the third component, and about 2.7 moles to about 3.3 moles of oxygen per 1 mole of the third component. For example, the third component includes about 1.8 moles to about 2.2 moles of lithium per 1 mole of the third component, about 0.8 moles to about 1.2 moles of the second metal per 1 mole of the third component, and about 2.8 moles to about 3.2 moles of oxygen per 1 mole of the third component. For example, the third component includes about 1.9 moles to about 2.1 moles of lithium per 1 mole of the third component, about 0.9 moles to about 1.1 moles of the second metal per 1 mole of the third component, and about 2.9 moles to about 3.1 moles of oxygen per 1 mole of the third component.
[0073] For example, the third component has a composition represented by Formula 3 below.
[0074] Formula 3
[0075] Li a M3 b O c
[0076] In Formula 3, M3 includes at least one of Zr, Al, Co, Mg, Mn, Si, Pd, Ni, Ti, Sn, Ir, Pt, and Ru, 1.9≤a≤2.1, 0.9≤b≤1.1, and 2.9≤a≤3.1.
[0077] Reference Figure 1B In the core 100 of the composite positive active material 300, the grain boundary 20 has a substantially linear shape, such as a straight line shape. Because the plurality of primary particles 10 adjacent to the grain boundary 20 have a polyhedral shape due to the first lithium transition metal oxide having a layered crystal structure, the grain boundary 20 formed between the adjacent primary particles 10 also has a linear shape, such as a straight line. Alternatively, the grain boundary 20 has a shape, such as a substantially curved or curved line. The radius of curvature of the curve is, for example, greater than 0 and less than about 1 m.
[0078] Reference Figure 1BIn composite positive active material 300, grain boundaries 20 are arranged, for example, in direction 21 parallel to the surfaces of adjacent primary particles 10. Further, for example, direction 21 in which grain boundaries 20 are arranged is different from tangent direction 101 of the surface of core 100 closest to grain boundaries 20.
[0079] Reference Figure 1B In the composite positive active material 300, the core 100 includes a first grain boundary 32 and a second grain boundary 33, the first grain boundary 32 and the second grain boundary 33 are directly located on the same primary particle 30, and the first grain boundary 32 and the second grain boundary 33 intersect at an angle (α) determined by the shape of the primary particle 30. The angle (α) at which the first grain boundary 32 and the second grain boundary 33 intersect is, for example, greater than 0° and less than about 180°, greater than about 10° and less than about 170°, greater than about 20° and less than about 160°, greater than about 30° and less than about 150°, greater than about 40° and less than about 140°, greater than about 50° and less than about 130°, greater than about 60° and less than about 120°, greater than about 70° and less than about 110°, or greater than about 80° and less than about 110°.
[0080] Reference Figure 1B In the composite positive active material 300, the core 100 includes a plurality of grain boundaries 32 and 42 adjacent to the plurality of primary particles 30 and 40, respectively. The plurality of grain boundaries 32 and 42 are arranged in directions 31 and 41 respectively parallel to the surfaces of the primary particles 30 and 40, respectively. The directions 31 and 41 in which the plurality of grain boundaries 32 and 42 are arranged are different from each other.
[0081] Reference Figure 1B , the core 100 of the composite positive active material 300 has an average grain boundary length of about 50nm to about 1000nm and an average grain boundary thickness of about 1nm to about 200nm. The length direction of the grain boundary refers to the direction parallel to the surface of each of the adjacent primary particles 20, 30 and 40, and the thickness direction of the grain boundary refers to the direction perpendicular to the surface of each of the primary particles 20, 30 and 40. The average grain boundary length is, for example, about 50nm to about 950nm, about 100nm to about 900nm, about 150nm to about 800nm, or about 200nm to about 700nm. The average grain boundary thickness is about 2nm to about 100nm, about 5nm to about 100nm, about 10nm to about 100nm, or about 20nm to about 100nm. When the average grain boundary length and the average grain boundary thickness are within the above range, the lithium battery including the composite positive active material provides further improved cycle characteristics and thermal stability. The average grain boundary length is the average value of the length d1 of the grain boundaries arranged in one direction. The average grain boundary thickness is an average value of the thicknesses d2 of the grain boundaries arranged in one direction.
[0082] In the composite positive electrode active material, the average particle size of the primary particles is, for example, about 50 nm to about 500 nm, about 50 nm to about 450 nm, about 50 nm to about 400 nm, about 50 nm to about 350 nm, about 50 nm to about 300 nm, about 50 nm to about 250 nm, or about 50 nm to about 200 nm. However, the average particle size of the primary particles is not limited to the above range, and can be adjusted within the range of providing improved cycle characteristics and thermal stability.
[0083] In the composite positive electrode active material, the average particle size of the core of the secondary particles in which the primary particles are aggregated is, for example, about 1 μm to about 30 μm, about 2 μm to about 28 μm, about 4 μm to about 26 μm, about 6 μm to about 24 μm, about 8 μm to about 22 μm, about 10 μm to about 20 μm, about 12 μm to about 18 μm, about 12 μm to about 16 μm, or about 13 μm to about 15 μm. However, the average particle size of the core is not limited to the above range, and can be adjusted within the range of providing improved cycle characteristics and thermal stability.
[0084] In the composite positive active material, the shell further includes, for example, the third component containing the second metal. In addition to the grain boundaries in the core, the third component may be added to the shell formed on the surface of the core. For example, the third component included in the shell has the same composition or the same crystal structure as the third component included in the grain boundaries in the core. For example, the third component included in the shell has a monoclinic crystal structure belonging to the C2 / m, C12 / c1, or C2 / c space group. The third component included in the shell has a composition represented by the above formula 3.
[0085] In the composite positive electrode active material, the first lithium transition metal oxide is doped with the second metal. Since the first lithium transition metal oxide is doped with the second metal, the structural stability of the first lithium transition metal oxide is improved.
[0086] In the composite positive electrode active material, the first lithium transition metal oxide may include lithium, nickel, the second metal, a third metal and oxygen. The third metal refers to a metal other than lithium, nickel and the second metal.
[0087] In the composite cathode active material, the first lithium transition metal oxide may include from about 0.1 mole to about 1.3 moles of lithium per 1 mole of the first lithium transition metal oxide, from about 0.7 mole to about 0.99 mole of nickel per 1 mole of the first lithium transition metal oxide, from about 0.001 mole to about 0.01 mole of the second metal per 1 mole of the first lithium transition metal oxide, from about 0.01 mole to about 0.3 mole of the third metal per 1 mole of the first lithium transition metal oxide, and from about 1.7 moles to about 2.3 moles of oxygen per 1 mole of the first lithium transition metal oxide.
[0088] For example, the first lithium transition metal oxide is represented by Formula 4 below.
[0089] Formula 4
[0090] Li a M4O 2-α X α
[0091] In Formula 4, 0.9 ≤ a ≤ 1.1, 0 ≤ α < 2, M4 includes nickel, the second metal, and the third metal, where the third metal includes at least one element of Groups 2 to 13 other than nickel and the second metal, the amount of nickel included in M4 is about 70 mole % or greater, based on the total amount of M4, and X is at least one of F, S, and P. The first lithium transition metal oxide represented by Formula 4 includes a doped second metal.
[0092] For example, the first lithium transition metal oxide is represented by Formula 5 below.
[0093] Formula 5
[0094] Li a Ni b M5 c M6 d M7 e O 2-α X α
[0095] In Formula 5, 0.9 ≤ a ≤ 1.1, 0.7 < b < 1.0, 0 < c < 0.3, 0 < d < 0.3, 0 ≤ e < 0.1, b + c + d + e = 1, 0 ≤ α < 2, M5, M6, and M7 are different from each other and each independently includes at least one of cobalt (Co), manganese (Mn), zirconium (Zr), aluminum (Al), rhenium (Re), vanadium (V), chromium (Cr), iron (Fe), boron (B), ruthenium (Ru), titanium (Ti), niobium (Nb), molybdenum (Mo), magnesium (Mg), and platinum (Pt), and X is at least one of F, S, and P. The first lithium transition metal oxide represented by Formula 5 includes a doped second metal.
[0096] For example, the first lithium transition metal oxide is represented by Formula 6 or 7 below.
[0097] Formula 6
[0098] Li a Ni b Co c Mn d M8 e O 2-α X α
[0099] Formula 7
[0100] Li a Ni b Co c Al d M8 e O 2-α X α
[0101] In Formulas 6 and 7, a, b, c, d, e, and α are independently 0.9 ≤ a ≤ 1.1, 0.7 < b < 1.0, 0 < c < 0.1, 0 < d < 0.1, 0 ≤ e < 0.01, b + c + d + e = 1, 0 ≤ α < 2, M8 includes at least one of zirconium (Zr), aluminum (Al), vanadium (V), chromium (Cr), iron (Fe), rhenium (Re), boron (B), ruthenium (Ru), titanium (Ti), niobium (Nb), molybdenum (Mo), magnesium (Mg), and platinum (Pt), and X is at least one of F, S, and P. The first lithium transition metal oxide represented by Formula 6 or 7 includes a doped second metal.
[0102] In the composite cathode active material, the first lithium transition metal oxide includes at least one of the following: a first layered structure crystal phase belonging to the C2 / m space group and a second layered structure crystal phase belonging to the R-3m space group. For example, the first lithium transition metal oxide may be a composite of the first layered structure crystal phase and the second layered structure crystal phase.
[0103] For example, the first lithium transition metal oxide includes a first layered structure crystal phase having a composition represented by Formula 8a and belonging to the C2 / m space group and a second layered structure crystal phase having a composition represented by Formula 8b and belonging to the R-3m space group.
[0104] Formula 8a
[0105] Li 2 MnO 3
[0106] Formula 8b
[0107] LiMO 2-α X α
[0108] In Formulas 8a and 8b, M includes Ni and one or more of the following elements: cobalt (Co), manganese (Mn), vanadium (V), chromium (Cr), iron (Fe), zirconium (Zr), rhenium (Re), aluminum (Al), boron (B), ruthenium (Ru), titanium (Ti), niobium (Nb), molybdenum (Mo), magnesium (Mg), and platinum (Pt), X is at least one of F, S, and P, and 0 ≤ α < 2. The amount of Ni included in M can be 70 mol% or more, or about 71 mol% to about 99 mol%, about 75 mol% to about 98 mol%, or about 78 mol% to about 90 mol%, based on the total transition metal content of the first layered structure crystal phase, or about 71 mol% to about 99 mol%, about 75 mol% to about 98 mol%, or about 78 mol% to about 90 mol%, based on the total transition metal content of the first lithium transition metal oxide. For example, the second layered structure crystal phase represented by Formula 8b includes a doped second metal.
[0109] For example, the first lithium transition metal oxide is represented by the following Formula 8c.
[0110] Formula 8c
[0111] aLi 2 MnO 3 ·(1 - a)LiMO 2-α X α
[0112] In Formula 8c, 0 < a < 1, 0 ≤ α < 2, M includes at least two of the following elements: nickel (Ni), cobalt (Co), manganese (Mn), zirconium (Zr), aluminum (Al), rhenium (Re), vanadium (V), chromium (Cr), iron (Fe), boron (B), ruthenium (Ru), titanium (Ti), niobium (Nb), molybdenum (Mo), magnesium (Mg), and platinum (Pt), and X is at least one of F, S, and P. M can include at least Ni. The amount of Ni in M can be 70 mol% or more, or about 71 mol% to about 99 mol%, about 75 mol% to about 98 mol%, or about 78 mol% to about 90 mol%, based on the total transition metal content of the first layered structure crystal phase, or about 71 mol% to about 99 mol%, about 75 mol% to about 98 mol%, or about 78 mol% to about 90 mol%, based on the total transition metal content of the first lithium transition metal oxide. The first lithium transition metal oxide represented by Formula 8c includes a doped second metal.
[0113] The positive electrode according to another embodiment includes the above composite positive electrode active material. Since the positive electrode includes the above composite positive electrode active material, the cycle characteristics and thermal stability are improved.
[0114] For example, the positive electrode is prepared by the following exemplary method. However, the method is not limited thereto and may be modified.
[0115] First, the composite positive active material, conductive agent, binder and solvent are mixed to prepare a positive active material composition. The prepared positive active material composition can be directly coated on an aluminum current collector and dried to prepare a positive plate having a positive active material layer. Alternatively, the positive active material composition is cast on a separate carrier, and the film peeled from the carrier is stacked on an aluminum current collector to prepare a positive plate having a positive active material layer.
[0116] The conductive agent may be, but is not limited to: carbon black, graphite particles, natural graphite, artificial graphite, acetylene black, Ketjen black, carbon fiber; carbon nanotubes; metals such as copper, nickel, aluminum and silver, each of which is used in the form of powder, fiber or tube; or conductive polymers such as polyphenylene derivatives, and any suitable material for the conductive agent may also be used.
[0117] The binder may be a vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene (PTFE), a mixture thereof, or a styrene-butadiene rubber polymer, and the solvent may be N-methylpyrrolidone (NMP), acetone, or water. However, the binder and the solvent are not limited thereto, and any suitable material for the binder and the solvent may also be used.
[0118] A plasticizer or a pore former may be further added to the positive active material composition to form pores in the electrode plate.
[0119] The amounts of the composite positive electrode active material, the conductive agent, the binder and the solvent used in the positive electrode are the same as those used in lithium batteries. Depending on the purpose and configuration of the lithium battery, at least one of the conductive agent, the binder and the solvent may be omitted.
[0120] Also, the positive electrode may further include another positive electrode active material in addition to the above-mentioned composite positive electrode active material.
[0121] The additional positive electrode active material may be any suitable lithium-containing metal oxide. For example, a composite oxide of lithium and at least one of the following metals may be used: cobalt, manganese, nickel, and any suitable combination thereof. For example, a compound represented by the following formula: Li a A 1-b B' b D 2 (where 0.90≤a≤1 and 0≤b≤0.5); Li a E 1-b B' b O 2-c D c(where 0.90≤a≤1, 0≤b≤0.5, and 0≤c≤0.05); LiE 2-b B' b O 4-c D c (where 0≤b≤0.5 and 0≤c≤0.05); Li a Ni 1-b-c Co b B' c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Co b B' c O 2-α F' α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Co b B' c O 2-α F' 2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Mn b B' c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Mn b B' c O 2-α F' α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Mn b B' c O 2-α F' 2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni b E c G d O 2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, and 0.001≤d≤0.1); Li a Ni b Co c Mnd G e O 2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, and 0.001≤e≤0.1); Li a NeG b O 2 (where 0.90≤a≤1 and 0.001≤b≤0.1); Li a CoG b O 2 (where 0.90≤a≤1 and 0.001≤b≤0.1); Li a MnG b O 2 (where 0.90≤a≤1 and 0.001≤b≤0.1); Li a Mn 2 G b O 4 (where 0.90≤a≤1 and 0.001≤b≤0.1); QO 2 ;;QS 2 ;LiQS 2 ; V 2 O 5 ;LiV 2 O 5 ;LiI'O 2 ;LiNiVO 4 ;Li (3-f) J 2 (PO 4 ) 3 (where 0≤f≤2); Li (3-f) Fe 2 (PO 4 ) 3 (where 0≤f≤2); and LiFePO 4 .
[0122] In the formula representing the above-mentioned compound, A is Ni, Co, Mn, or any combination thereof; B' is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or any combination thereof; D is O, F, S, P, or any combination thereof; E is Co, Mn, or any combination thereof; F' is F, S, P, or any combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or any combination thereof; Q is Ti, Mo, Mn, or any combination thereof; I' is Cr, V, Fe, Sc, Y, or any combination thereof; and J is V, Cr, Mn, Co, Ni, Cu, or any combination thereof.
[0123] The above-mentioned compound with a coating added to its surface or a mixture of the above-mentioned compound and a compound with a coating can be used. The coating added to the surface of the above-mentioned compound may include a compound of a coating element such as an oxide, hydroxide, oxyhydroxide, oxycarbonate or hydroxycarbonate of the coating element. The compound constituting the coating is amorphous or crystalline. The coating element included in the coating may be Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr or any mixture thereof. The coating can be formed by using any method that does not adversely affect the physical properties of the positive active material. Examples of coating methods include spraying and impregnation. The coating method is well known in the art, and therefore its detailed description will be omitted.
[0124] For example, the positive electrode includes the above-mentioned composite positive electrode active material and an olivine-based positive electrode active material.
[0125] For example, the olivine-based positive active material is represented by Formula 9 below.
[0126] Formula 9
[0127] Li x M8 y M9 z PO 4-α X α
[0128] In Formula 9, 0.90≤x≤1.1, 0≤y≤0.9, 0≤z≤0.5, 1-yz≥0, 0≤α≤2, M8 includes at least one metal of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Al, Mg, Zr, and B, M9 includes at least one element of Mg, Ca, Sr, Ba, Ti, Zr, Nb, Mo, W, Zn, Al, Si, Ni, Mn, Cr, Fe, V, and rare earth elements, and X is at least one of F, S, and P.
[0129] An example of the olivine-based positive electrode active material is LiFePO 4 、LiNiPO 4 、LiMnPO 4 、LiCoPO 4 wait.
[0130] For example, the amount of the olivine-based positive active material included in the positive electrode is about 10 weight percent (wt%) or less, about 9 weight % or less, about 8 weight % or less, about 7 weight % or less, about 6 weight % or less, or about 5 weight % or less, based on the total weight of the positive active material. For example, the amount of the olivine-based positive active material included in the positive electrode is about 1 weight % to about 10 weight %, about 1 weight % to about 9 weight %, about 1 weight % to about 8 weight %, about 1 weight % to about 7 weight %, about 1 weight % to about 6 weight %, or about 1 weight % to about 5 weight %, based on the total weight of the positive active material. For example, the amount of the olivine-based positive active material included in the positive electrode is about 1 weight part to about 10 weight parts, about 1 weight part to about 9 weight parts, about 1 weight part to about 8 weight parts, about 1 weight part to about 7 weight parts, about 1 weight part to about 6 weight parts, or about 1 weight part to about 5 weight parts, based on 100 weight parts of the positive active material. When the positive electrode further includes the olivine-based positive active material within the above range, cycle characteristics and mix density of a lithium battery are further improved.
[0131] A lithium battery according to another embodiment includes a positive electrode including the above-mentioned composite positive electrode active material.
[0132] When the lithium battery includes a positive electrode including the composite positive electrode active material, improved cycle characteristics and thermal stability are provided.
[0133] The lithium battery is manufactured, for example, by the following exemplary method. However, the method is not limited thereto and may be modified.
[0134] First, a positive electrode is prepared according to the above method for preparing a positive electrode.
[0135] Next, the negative electrode is prepared as follows. For example, the negative electrode is prepared in a method substantially the same as the method for preparing the positive electrode, except that a negative electrode active material is used instead of the composite positive electrode active material. In addition, in the negative electrode active material composition, a conductive agent, a binder and a solvent substantially the same as those of the positive electrode may also be used.
[0136] For example, the negative electrode active material, the conductive agent, the binder and the solvent are mixed to prepare the negative electrode active material composition, and the negative electrode active material composition is directly coated on a copper current collector to prepare a negative electrode plate. Alternatively, the prepared negative electrode active material composition is cast on a separate carrier, and the negative electrode active material film separated from the carrier is laminated on a copper current collector to prepare a negative electrode plate.
[0137] The negative electrode active material can be any suitable material used as the negative electrode active material in a lithium battery in the art. For example, the negative electrode active material includes lithium metal, a metal capable of alloying with lithium, a transition metal oxide, a non-transition metal oxide, and a carbonaceous material.
[0138] For example, the metal capable of alloying with lithium can be Si, Sn, Al, Ge, Pb, Bi, Sb, a Si-Y' alloy (where Y' is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, or any combination thereof, excluding Si), or a Sn-Y' alloy (where Y' is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, or any combination thereof, excluding Sn). The element Y' is, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, or any combination thereof.
[0139] For example, the transition metal oxide is a lithium titanium oxide, a vanadium oxide, and a lithium vanadium oxide.
[0140] For example, the non-transition metal oxide is SnO 2 、SiO x (0 < x < 2), etc.
[0141] For example, the carbonaceous material is crystalline carbon, amorphous carbon, or any mixture thereof. The crystalline carbon is, for example, graphite such as natural graphite or artificial graphite, which is in the form of being shapeless, plate, sheet, spherical, or fibrous. The amorphous carbon is, for example, soft carbon (carbon calcined at low temperature), hard carbon, mesophase pitch carbonization product, or calcined coke.
[0142] The amounts of the negative electrode active material, the conductive agent, the binder, and the solvent are the same as those used in a lithium battery. Depending on the use and configuration of the lithium battery, at least one of the conductive agent, the binder, and the solvent may not be used.
[0143] Subsequently, a separator to be inserted between the positive electrode and the negative electrode is prepared.
[0144] Any suitable separator used in the art for lithium batteries can be used. For example, any separator having low resistance to ion migration of electrolytes and excellent electrolyte retention can be used. For example, the separator can be glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or any combination thereof, each of which is a nonwoven fabric or a woven fabric. For example, a windable separator including polyethylene or polypropylene can be used in lithium ion batteries, and a separator having excellent organic electrolyte retention can be used in lithium ion polymer batteries.
[0145] The separator is prepared according to the following exemplary method. However, the method is not limited thereto and may be modified.
[0146] First, a polymer resin, a filler and a solvent are mixed to prepare a separator composition. The separator composition is directly coated on an electrode and dried to prepare a separator. Alternatively, the separator composition is cast and dried on a support, and then a separator film separated from the support is laminated on an electrode to form a separator.
[0147] The polymer used to prepare the separator is not particularly limited, and any suitable polymer used as a binder for electrode plates may also be used. For example, vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, or any mixture thereof may be used.
[0148] Subsequently, an electrolyte is prepared.
[0149] For example, the electrolyte may be an organic electrolyte solution. For example, the electrolyte solution is prepared by dissolving a lithium salt in an organic solvent.
[0150] Any suitable organic solvent used in the art can be used. For example, the organic solvent is propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, cyclopentane, ethylene dichloride, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or any mixture thereof.
[0151] The lithium salt may also be any suitable lithium salt used in the art. For example, the lithium salt is LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiCF3 SO 3 、Li(CF 3 SO 2 ) 2 N, LiC 4 F 9 SO 3 、LiAlO 2 、LiAlCl 4 、LiN(C x F 2x+1 SO 2 )(C y F 2y+1 SO 2 )(wherein x and y are natural numbers), LiCl, LiI or any mixture thereof.
[0152] Alternatively, the electrolyte may be a solid electrolyte. For example, the solid electrolyte is boron oxide, lithium oxynitride, etc. However, the solid electrolyte is not limited thereto, and any known solid electrolyte may be used. The solid electrolyte may be formed on the negative electrode by sputtering, etc., or a separate solid electrolyte sheet may be stacked on the negative electrode.
[0153] like Figure 6 As shown in FIG, the lithium battery 1 includes a positive electrode 3, a negative electrode 2, and a separator 4. The positive electrode 3, the negative electrode 2, and the separator 4 may be wound or folded and then housed in a battery case 5. An organic electrolyte solution is injected into the battery case 5 and the battery case 5 is sealed by a cap assembly 6, thereby completing the manufacture of the lithium battery 1. The battery case 5 may have a cylindrical shape. However, the shape of the battery case 5 is not limited thereto, and a rectangular shape or a thin film shape may also be used.
[0154] The pouch-type lithium battery includes at least one battery assembly. A separator is inserted between the positive electrode and the negative electrode to form the battery assembly. The battery assembly is stacked in a double-cell battery structure, impregnated with an organic electrolyte solution, contained in a bag, and sealed to complete the manufacture of the pouch-type lithium battery. Multiple battery assemblies can be stacked to form a battery pack, which can be used in any device that benefits from high capacity and output power, such as laptops, smart phones, and electric vehicles.
[0155] Due to the excellent life characteristics and high rate properties, lithium batteries are used in, for example, electric vehicles (EVs). For example, lithium batteries are used in hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs). Moreover, lithium batteries are used in, for example, electric bicycles and power tools.
[0156] The method for preparing a composite positive electrode active material includes: providing, for example, preparing a first lithium transition metal oxide; mixing the first lithium transition metal oxide with a first metal precursor to prepare a first composition; mixing the first composition of the first lithium transition metal oxide with a P precursor including phosphorus to prepare a second composition; drying the second composition; and heat treating the dried second composition at a temperature of about 400°C to about 1000°C in an oxidizing atmosphere to prepare the composite positive electrode active material.
[0157] For example, the preparation of the first composition and the preparation of the second composition can be carried out by a wet method using a solvent. The first composition and the second composition respectively include solvents for dissolving the first metal precursor and the P precursor, and any suitable solvent used in the art can be used without limitation. For example, the solvent is distilled water.
[0158] The first metal precursor may be a nitrate, an oxychloride, or an oxynitrate of the first metal. However, the first metal precursor is not limited thereto, and may be any suitable dissociated salt including the first metal and used in the art. Examples of the first metal precursor include Co(NO 3 ) 2 6H 2 O and Mg(NO 3 ) 2 6H 2 O. In the first composition, for example, the hydroxide form of the first metal is deposited on the surface of the first lithium transition metal oxide. Examples of the hydroxide form of the first metal include Co(OH) 2 and Mg(OH) 2 .
[0159] The P precursor may be an ammonium or metal phosphate. However, the P precursor is not limited thereto and may be any suitable dissociated salt including phosphorus (P) and used in the art. Examples of the P precursor include (NH 4 ) 2 HPO 4 and (NH 4 ) 3 PO 4 In the second composition, a precursor of the second composition is deposited on the first lithium transition metal oxide.
[0160] The oxidizing atmosphere may be an atmosphere comprising oxygen or air. The oxidizing atmosphere comprises oxygen, air, or any combination thereof, such as air with an increased amount of oxygen.
[0161] In the first composition, the amount of the first metal precursor may be about 30 parts by weight or less, about 20 parts by weight or less, or about 10 parts by weight or less, based on 100 parts by weight of the first lithium transition metal oxide. In the first composition, the amount of the solvent may be 300 parts by weight or less, 200 parts by weight or less, or 100 parts by weight or less, based on 100 parts by weight of the first lithium transition metal oxide. In the second composition, the amount of the P precursor may be 30 parts by weight or less, 20 parts by weight or less, or 10 parts by weight or less, based on 100 parts by weight of the first lithium transition metal oxide. In the second composition, the amount of the solvent may be 300 parts by weight or less, 200 parts by weight or less, or 100 parts by weight or less, based on 100 parts by weight of the first lithium transition metal oxide.
[0162] For example, the heat treatment is carried out at a temperature of about 400°C to about 1000°C, about 500°C to about 900°C, about 600°C to about 800°C, or about 700°C to about 750°C. The heat treatment time is, for example, about 3 hours to about 20 hours, about 3 hours to about 15 hours, about 3 hours to about 10 hours, about 3 hours to about 7 hours, or about 4 hours to about 6 hours. The heating rate to reach the heat treatment temperature is, for example, about 1°C / minute to about 10°C / minute. When the heat treatment temperature, heat treatment time and heating rate are within the above ranges, a shell comprising a first layer formed on the core and a second layer formed on the first layer is prepared.
[0163] In the method for preparing the composite positive electrode active material, the preparation of the first lithium transition metal oxide includes: preparing a precursor mixture of the first lithium transition metal oxide precursor and a second metal precursor; and heat treating the mixture at a temperature of about 400°C to about 1000°C in an oxidizing atmosphere to prepare the first lithium transition metal oxide.
[0164] For example, the preparation of the mixture can be carried out by a dry method without using a solvent. The mixture may be a dry powder obtained by mixing a powder of a precursor of the first lithium transition metal oxide and a powder of the second metal precursor. Alternatively, the preparation of the mixture is carried out by a wet method using a solvent. The mixture includes a solvent that dissolves the precursor of the first lithium transition metal oxide and the second metal precursor, and any known solvent can be used without limitation. For example, the solvent is distilled water. By the wet method, the third component including the second metal is more densely included in the grain boundaries between the primary particles.
[0165] The oxidizing atmosphere refers to an atmosphere including oxygen or air. The oxidizing atmosphere includes oxygen, air, or any combination thereof, such as air with an increased amount of oxygen.
[0166] The second metal precursor may be an oxide or hydroxide of the second metal. However, the second metal precursor is not limited thereto and may be any material including the second metal and used in the art. Examples of the second metal precursor include ZrO 2 and Al 2 O 3 .
[0167] In the mixture, an amount of the second metal precursor is 30 parts by weight or less, 20 parts by weight or less, or 10 parts by weight or less, based on 100 parts by weight of the first lithium transition metal oxide precursor.
[0168] The heat treatment is carried out, for example, at a temperature of about 400°C to about 1000°C, about 500°C to about 900°C, about 600°C to about 800°C, or about 700°C to about 750°C. The heat treatment time is, for example, about 3 hours to about 20 hours, about 3 hours to about 15 hours, about 3 hours to about 10 hours, about 3 hours to about 7 hours, or about 4 hours to about 6 hours. The heating rate to reach the heat treatment temperature is, for example, about 1°C / minute to about 10°C / minute. When the heat treatment temperature, heat treatment time and heating rate are within the above range, a third component including a second metal is formed in the grain boundaries between the primary particles, and the first lithium transition metal oxide is doped with the second metal.
[0169] Hereinafter, the embodiments will be described in detail with reference to the following examples and comparative examples. However, these examples and comparative examples are not intended to limit the purpose and scope of one or more embodiments.
[0170] Example
[0171] Preparation of composite positive electrode active materials
[0172] Example 1: Ni88+Al-Zr doping, Li 2 ZrO 3 Grain boundary coating + Co / Mg:P = 0.25 wt %: 0.25 wt %, and double layer coating
[0173] Core preparation
[0174] Zirconium oxide (ZrO 2 ) and aluminum oxide (Al 2 O 3 ), Ni as the first lithium transition metal oxide precursor 0.88 Co 0.08 Mn 0.04 (OH) 2 , and LiOH·H as a lithium precursor 2O is mixed in a molar ratio for obtaining a core having the following composition. 0.88 Co 0.08 Mn 0.04 (OH) 2 and lithium precursor LiOH·H 2 O was mixed in a molar ratio of 1:1.09. The mixture was placed in a furnace and subjected to a primary heat treatment at 720° C. for 5 hours while flowing oxygen to prepare a core.
[0175] By the primary heat treatment, a Li(Ni)-doped with Al and Zr as the first lithium transition metal oxide is obtained. 0.88 Co 0.08 Mn 0.04 ) 1-x-y Al x Zr y O 2 Core (where x=0.001 and y=0.0025).
[0176] Furthermore, Li having a monoclinic crystal structure is formed on the surface of the core (ie, the polycrystalline secondary particle) and in the grain boundaries between the plurality of primary particles. 2 ZrO 3 Coating layer.
[0177] Shell preparation
[0178] The precursor was prepared by: Co(NO 3 ) 2 6H 2 O and Mg(NO 3 ) 2 6H 2 O is mixed in a molar ratio of 3:2 so that in the first layer of the composite positive electrode active material, the sum of the amounts of Co and Mg is 0.25 parts by weight based on 100 parts by weight of the first lithium transition metal oxide. The precursor is added to 10 parts by weight of distilled water and stirred at room temperature (25° C.) for 1 minute to prepare a first aqueous solution.
[0179] Prepare NH 4 H 2 PO 4 , so that in the second layer of the composite positive electrode active material, the amount of P is 0.25 parts by weight based on 100 parts by weight of the first lithium transition metal oxide, and then added to 10 parts by weight of distilled water, and stirred at room temperature (25°C) for 1 minute to prepare a second aqueous solution.
[0180] 100 parts by weight of Li(Ni 0.88 Co 0.08 Mn 0.04 ) 1-x-y Alx Zr y O 2 The powder of the core (where x=0.001 and y=0.0025) was added to 90 parts by weight of distilled water to prepare a third aqueous solution. While stirring at room temperature for 10 minutes, the first aqueous solution and the second aqueous solution were sequentially added to the third aqueous solution to prepare a mixture.
[0181] The mixture was dried in an oven at 150° C. for 15 hours to prepare a dried product.
[0182] The dried product was added to a furnace and heat-treated at 720° C. for 5 hours while flowing oxygen to prepare a composite positive active material.
[0183] Including Co 3 O 4 and MgO first layer formed on Li(Ni 0.88 Co 0.08 Mn 0.04 ) 1-x-y Al x Zr y O 2 on the surface of the core (where x=0.001 and y=0.0025), and includes Li x CoPO 4 (where 0 <x<2)、Li 3 PO 4 and Co 3 (PO 4 ) 2 A second layer is formed on the first layer.
[0184] The sum of Co and Mg contained in the first layer was 0.25 parts by weight based on 100 parts by weight of the first lithium transition metal oxide, and the amount of P contained in the second layer was 0.25 parts by weight based on 100 parts by weight of the first lithium transition metal oxide.
[0185] Example 2: Ni88+Al-Zr doping, Li 2 ZrO 3 Grain boundary coating + Co / Mg:P = 0.50 wt %: 0.25 wt %, and double layer coating
[0186] A composite positive electrode active material was prepared in the same manner as in Example 1, except that: Co(NO 3 ) 2 6H 2 O and Mg(NO 3 ) 2 6H 2O are mixed in a molar ratio of 3:2 so that in the first layer of the composite positive electrode active material, the sum of the amounts of Co and Mg is 0.5 parts by weight based on 100 parts by weight of the first lithium transition metal oxide.
[0187] The sum of Co and Mg contained in the first layer was 0.5 parts by weight based on 100 parts by weight of the first lithium transition metal oxide, and the amount of P contained in the second layer was 0.25 parts by weight based on 100 parts by weight of the first lithium transition metal oxide.
[0188] Example 3: Ni88+Al-Zr doping, Li 2 ZrO 3 Grain boundary coating + Co / Mg:P = 0.75 wt %: 0.25 wt %, and double layer coating
[0189] A composite positive electrode active material was prepared in the same manner as in Example 1, except that: Co(NO 3 ) 2 6H 2 O and Mg(NO 3 ) 2 6H 2 O are mixed in a molar ratio of 3:2 so that in the first layer of the composite positive electrode active material, the sum of the amounts of Co and Mg is 0.75 parts by weight based on 100 parts by weight of the first lithium transition metal oxide.
[0190] The sum of Co and Mg contained in the first layer was 0.75 parts by weight based on 100 parts by weight of the first lithium transition metal oxide, and the amount of P contained in the second layer was 0.25 parts by weight based on 100 parts by weight of the first lithium transition metal oxide.
[0191] Example 4: Ni88+Al doping (without Zr)+Co / Mg:P=0.25 wt %:0.25 wt %, and double layer coating
[0192] A composite positive electrode active material was prepared in the same manner as in Example 1, except that in the preparation of the core, alumina (Al 2 O 3 ) as the second metal precursor instead of using zirconium oxide (ZrO 2 ).
[0193] Through a heat treatment, Al-doped Li(Ni 0.88 Co 0.08 Mn 0.04 ) 1-x Al x O 2 Core (where x=0.001).
[0194] The sum of Co and Mg contained in the first layer was 0.25 parts by weight based on 100 parts by weight of the first lithium transition metal oxide, and the amount of P contained in the second layer was 0.25 parts by weight based on 100 parts by weight of the first lithium transition metal oxide.
[0195] Comparative Example 1: Ni88 Core
[0196] The Li(Ni) prepared in the first heat treatment of Example 1 was used. 0.88 Co 0.08 Mn 0.04 ) 1-x-y Al x Zr y O 2 Powder of core (where x=0.001 and y=0.0025).
[0197] Comparative Example 2: Ni88 core + washing
[0198] 100 parts by weight of the Li(Ni) prepared in the first heat treatment of Example 1 0.88 Co 0.08 Mn 0.04 ) 1-x-y Al x Zr y O 2 After the powder of the core (where x=0.001 and y=0.0025) was added to 90 parts by weight of distilled water and the mixture was stirred, a washing process was performed once by filtering and separating the precipitate to remove residual lithium.
[0199] The separated precipitate was dried in an oven at 150° C. for 15 hours to prepare a dried product.
[0200] The dried product was added to a furnace and heat-treated at 720° C. for 5 hours while flowing oxygen to prepare a composite cathode active material.
[0201] Comparative Example 3: Ni88+Al-Zr doping, Li 2 ZrO 3 Grain boundary coating + Co / Mg:P = 0.75 wt %: 0.0 wt %, and single layer coating
[0202] The composite positive electrode active material was prepared in the same manner as in Example 1, except that: Co(NO 3 ) 2 6H 2 O and Mg(NO 3 ) 2 6H 2O is mixed in a molar ratio of 3:2, so that in the first layer of the composite positive electrode active material, the sum of the amounts of Co and Mg is 0.75 parts by weight based on 100 parts by weight of the first lithium transition metal oxide, and no NH 4 H 2 PO 4 of a second aqueous solution.
[0203] Including Co 3 O 4 and MgO first layer formed on Li(Ni 0.88 Co 0.08 Mn 0.04 ) 1-x-y Al x Zr y O 2 On the surface of the core (where x=0.001 and y=0.0025). No second layer is formed.
[0204] The sum of the amounts of Co and Mg is 0.75 parts by weight based on 100 parts by weight of the first lithium transition metal oxide.
[0205] Comparative Example 4: Ni88+Al-Zr doping, Li 2 ZrO 3 Grain boundary coating + Co / Mg:P = 0.25 wt%: 0.25 wt%, single layer composite coating
[0206] A composite positive active material was prepared in the same manner as in Example 1, except that in the preparation of the shell, the first aqueous solution and the second aqueous solution were simultaneously added to the third aqueous solution.
[0207] A composite layer including Co, Mn, and P is formed on Li(Ni 0.88 Co 0.08 Mn 0.04 ) 1-x-y Al x Zr y O 2 On the surface of the core (where x=0.001 and y=0.0025).
[0208] The sum of the amounts of Co and Mg is 0.25 parts by weight based on 100 parts by weight of the first lithium transition metal oxide, and the amount of P is 0.25 parts by weight based on 100 parts by weight of the first lithium transition metal oxide.
[0209] Reference Example 1: Ni88+Al-Zr doping, Li 2 ZrO 3 Grain boundary coating + Co / Mg:P = 0.25 wt %: 0.0 wt %, and single layer coating
[0210] The composite positive active material was prepared in the same manner as in Example 1, except that in the preparation of the shell, no NH 4 H 2 PO 4 of a second aqueous solution.
[0211] Including Co 3 O 4 and MgO first layer formed on Li(Ni 0.88 Co 0.08 Mn 0.04 ) 1-x-y Al x Zr y O 2 On the surface of the core (where x=0.001 and y=0.0025). No second layer is formed.
[0212] In the first layer, the sum of the amounts of Co and Mg was 0.25 parts by weight based on 100 parts by weight of the first lithium transition metal oxide. This configuration was prepared by removing the second layer from the composite positive active material according to Example 1 for comparison with Example 1.
[0213] Preparation of lithium battery (half-cell)
[0214] Example 5
[0215] Preparation of positive electrode
[0216] The composite positive active material prepared according to Example 1, a carbon conductive agent (Denka Black) and polyvinylidene fluoride (PVdF) were mixed in a weight ratio of 92:4:4 to prepare a mixture, and the mixture was mixed with N-methylpyrrolidone (NMP) in an agate mortar to prepare a slurry. The slurry was applied to a 15 μm thick aluminum current collector by bar coating, and the slurry was dried at room temperature, further dried in a vacuum at 120° C., rolled and punched to prepare a positive plate having a thickness of 55 μm.
[0217] Preparation of coin cell batteries
[0218] A coin cell was prepared using the prepared positive electrode plate, lithium metal as a counter electrode, a PTFE separator, and an electrolyte prepared by mixing 1.15 M LiPF 6 Dissolved in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) (3:4:3 by volume).
[0219] Embodiment 6-8
[0220] A coin cell was prepared in the same manner as in Example 5, except that the composite positive active materials prepared according to Examples 2 to 4, respectively, were used instead of the composite positive active material prepared according to Example 1.
[0221] Example 9: Addition of LFP
[0222] A coin cell was prepared in the same manner as in Example 5, except that 5 parts by weight of LiFePO 4 (LFP) was added to 100 parts by weight of the composite positive active material prepared according to Example 1.
[0223] Comparative Examples 5-8
[0224] A coin cell was prepared in the same manner as in Example 5, except that the composite positive active materials prepared according to Comparative Examples 1 to 4, respectively, were used instead of the composite positive active material prepared according to Example 1.
[0225] Preparation of lithium battery (full cell)
[0226] Example 10
[0227] Preparation of positive electrode
[0228] The composite positive active material prepared according to Example 1, a carbon conductive agent (Denka Black) and polyvinylidene fluoride (PVdF) were mixed in a weight ratio of 92:4:4, and the mixture was mixed with N-methylpyrrolidone (NMP) in an agate mortar to prepare a positive active material slurry. The slurry was applied to a 15 μm thick aluminum current collector by bar coating, and the coated slurry was dried at room temperature, further dried in a vacuum at 120° C., rolled and punched to prepare a positive plate having a thickness of 55 μm.
[0229] Preparation of negative electrode
[0230] Graphite particles having an average particle size of 25 μm, styrene butadiene rubber (SBR) binder (ZEON) and carboxymethyl cellulose (CMC, NIPPON A&L) were mixed in a weight ratio of 97:1.5:1.5, and the mixture was added to distilled water and stirred for 60 minutes using a mechanical stirrer to prepare a negative active material slurry. The slurry was applied to a 10 μm thick copper current collector using a scraper, and the slurry was dried in a hot air dryer at 100° C. for 0.5 hours, further dried at 120° C. in a vacuum for 4 hours, rolled and punched to prepare a negative plate having a thickness of 65 μm.
[0231] Preparation of coin cell batteries
[0232] A coin cell was prepared using the positive and negative plates prepared as described above, a PTFE separator, and an electrolyte prepared as follows: 1.15 M LiPF 6 Dissolved in a mixed solvent of EC, EMC, and DMC (3:4:3 volume ratio).
[0233] Examples 11-13
[0234] A coin cell was prepared in the same manner as in Example 10, except that the composite positive active materials prepared according to Examples 2 to 4, respectively, were used instead of the composite positive active material prepared according to Example 1.
[0235] Example 14: Addition of LFP
[0236] A coin cell was prepared in the same manner as in Example 10, except that 5 parts by weight of LiFePO 4 Add to 100 parts by weight of the composite positive electrode active material prepared according to Example 1.
[0237] Comparative Examples 9-12
[0238] Coin cells were prepared in the same manner as in Example 10, except that the composite positive active materials prepared according to Comparative Examples 1 to 4 were used instead of the composite positive active material prepared according to Example 1.
[0239] Evaluation Example 1: Evaluation of XRD Spectra
[0240] The X-ray diffraction (XRD) spectra of the composite positive electrode active materials prepared according to Reference Example 1 and Example 1 were obtained, and the results are shown in Figure 2A and 2B In. XRD spectra were obtained using Cu Kα radiation.
[0241] like Figure 2A As shown in, in the XRD spectrum of the composite positive electrode active material according to Reference Example 1 in which only the first layer is formed as a coating layer, only the peak representing the phase having a layered crystal structure belonging to the R-3m space group was observed. Therefore, it was confirmed that the component including the first layer had a first phase having a layered crystal structure belonging to the R-3m space group.
[0242] like Figure 2B As shown in, in the XRD spectrum of the composite positive active material according to Example 1 in which the second layer is additionally formed on the first layer as a coating layer, in addition to the peak representing the layered crystal structure, another peak is observed at a diffraction angle (2θ) of about 20° to about 35°. Therefore, it is confirmed that a second phase that is structurally different from the first phase included in the first layer is additionally formed.
[0243] Through Rietveld analysis, it was confirmed that the first layer includes Co 3 O 4 phase and MgO phase, and the second layer includes Li 3 PO 4 phase, Li a Co b (PO 4 ) c phase (where 0.5 < a < 1.5, 0.9 < b < 1.5, and 0.9 < c < 1.5), and Co 3 (PO 4 ) 2 phase.
[0244] Evaluation Example 2: Composition Evaluation of the Interior and Surface of the Core
[0245] Figures 3A-3C High-angle annular dark-field (HAADF) scanning transmission electron microscopy (STEM) images and energy-dispersive X-ray spectroscopy (EDS) images of a cross-section of a composite cathode active material prepared according to Reference Example 1, which includes a core composed of secondary particles formed by aggregation of a plurality of primary particles and a first layer formed on the core.
[0246] Figures 4A-4D HAADF STEM images and EDS images of a cross-section of a composite cathode active material prepared according to Example 1, which includes a core composed of secondary particles formed by aggregation of a plurality of primary particles and a first layer and a second layer each formed on the core.
[0247] As Figures 3A-3C shown, it was confirmed that a first layer including Co and Mg was formed on the core.
[0248] It was also confirmed that the concentration of Co and / or Mg included in the first layer is higher than the concentration of Co and / or Mg included in the primary particles. Referring to Figure 3B and 3C , the higher the concentration of a metal, the brighter the color corresponding to that metal. That is, it was confirmed that a coating layer including a high concentration of Co and Mg was formed on the primary particles included in the core.
[0249] As Figures 4A-4D shown, it was confirmed that a second layer including Co and P was formed on the first layer. Although not shown in the figure, it was also confirmed that the second layer has a mixed phase including Li, Co, P, and O.
[0250] As Figure 4A and 4B shown, the thickness of the second layer is greater than the thickness of the first layer. The thickness of the first layer is about 20 nm, and the thickness of the second layer is about 100 nm.
[0251] Although not shown in the figure, it was confirmed through additional high-resolution analysis that a separate phase including Zr was formed in the grain boundaries between the primary particles included in the core and on the surface of the core (i.e., the polycrystalline secondary particle). The separate phase was Li+ with a monoclinic crystal structure belonging to the C2 / m space group. 2 ZrO 3 Mutually.
[0252] Evaluation Example 3: Evaluation of the amount of residual lithium
[0253] The amounts of residual lithium on the surfaces of the composite cathode active materials prepared according to Comparative Examples 1 to 3 and Example 1 were measured, and some of the results are shown in Table 1 below.
[0254] The amount of residual lithium on the surface was evaluated by measuring the amount of Li remaining on the surface of the composite positive electrode active material using a wet method (or titration method). 2 CO 3 and the amount of Li in LiOH.
[0255] Specifically, reference may be made to the method disclosed in paragraph
[0054] of Japanese Patent Laid-Open Publication No. 2016-081903 (the contents of which are incorporated herein by reference in their entirety).
[0256] Table 1
[0257] Residual lithium content [ppm] Comparative Example 1 6723 Comparative Example 2 1160 Comparative Example 3 1189 Example 1 1142
[0258] As shown in Table 1, the amount of residual lithium on the surface of the composite cathode active material according to Example 1 was reduced when compared with the amount of residual lithium on the surface of the composite cathode active materials according to Comparative Examples 1 to 3.
[0259] It is considered that the lithium remaining on the first lithium transition metal oxide reacts sequentially with the precursor of the first component and the precursor of the second component, thereby forming a multi-layer coating layer on the core.
[0260] Therefore, since gas generation is suppressed and side reactions with the electrolyte solution are prevented during charging and discharging of a lithium battery including the composite positive electrode active material according to Example 1, the lithium battery can have improved lifespan characteristics when compared with lithium batteries including the composite positive electrode active materials according to Comparative Examples 1-3, respectively.
[0261] Evaluation Example 4: DSC Measurement of Composite Cathode Active Material
[0262] The thermal spectra of the composite positive active materials prepared according to Example 1 and Comparative Example 3 were obtained from 30° C. to 350° C. using a differential scanning calorimeter (DSC), and the results are shown in the following Tables 2 and Figure 5 middle.
[0263] Table 2
[0264] Amount of heat generated [J / g] Example 1 1776 Comparative Example 3 2137
[0265] As shown in Table 2, the amount of heat generated in the composite cathode active material according to Example 1 having the multi-layer coating layer was reduced when compared with the amount of heat generated in the composite cathode active material according to Comparative Example 3 having the single-layer coating layer.
[0266] Moreover, if Figure 5 As shown in , the composite cathode active material according to Example 1 exhibits a higher starting temperature at which thermal decomposition is initiated, compared with the composite cathode active material according to Comparative Example 3.
[0267] Therefore, it was confirmed that, when compared with the composite cathode active material according to Comparative Example 3, the thermal stability of the composite cathode active material according to Example 1 was improved.
[0268] Evaluation Example 5: Charge / Discharge Characteristics at Room Temperature
[0269] The lithium batteries prepared according to Examples 5-8 and Comparative Examples 5-8 were charged at a constant current rate of 0.1C at 25°C until the voltage reached 4.35V (relative to Li), and then the charging process was terminated at a current rate of 0.05C while maintaining a voltage of 4.35V in a constant voltage mode. Subsequently, the lithium battery was discharged at a constant current rate of 0.1C until the voltage reached 2.8V (relative to Li) (1st cycle, formation cycle).
[0270] The C-rate is the discharge rate of the cell and is obtained by dividing the total capacity of the cell by the total discharge time of 1 hour, for example, for a cell with a discharge capacity of 1.6 ampere-hours, the C-rate would be 1.6 amperes.
[0271] The lithium battery undergoing the first cycle was charged at a constant current rate of 1.0C at 25°C until the voltage reached 4.35V (relative to Li), and then the charging process was terminated at a current rate of 0.05C while maintaining a voltage of 4.35V in a constant voltage mode. Subsequently, the lithium battery was discharged at a current rate of 0.2C until the voltage reached 2.8V (relative to Li) (second cycle).
[0272] The lithium battery undergoing the second cycle was charged at a constant current rate of 1C at 25°C until the voltage reached 4.35V (relative to Li), and then the charging process was terminated at a current rate of 0.05C while maintaining a voltage of 4.35V in a constant voltage mode. Subsequently, the lithium battery was discharged at a current rate of 1C until the voltage reached 2.8V (relative to Li) (the third cycle), and the cycle was repeated 50 times under the same conditions until the 52nd cycle.
[0273] The lithium battery was allowed to rest for 10 minutes after each charge / discharge cycle.
[0274] Some of the charge / discharge tests are shown below in Table 3. The capacity retention at the 52nd cycle is defined as Equation 1.
[0275] Equation 1
[0276] Capacity retention rate [%] = [discharge capacity at the 52nd cycle / discharge capacity at the 3rd cycle] × 100%
[0277] Table 3
[0278]
[0279] As shown in Table 3, the lithium batteries according to Examples 5 and 6 had improved lifespan characteristics without substantial capacity reduction when compared with the lithium batteries according to Comparative Examples 6-8.
[0280] It is considered that the improvement in the lifespan characteristics of the lithium batteries according to Examples 5 and 6 is obtained because the surface of the composite cathode active material included in the lithium battery is stabilized by the double-layer coating and the side reaction with the electrolyte solution is thereby suppressed.
[0281] It is also considered that the second layer additionally included in each of the composite positive electrode active materials of the lithium batteries according to Examples 5 and 6 more effectively suppresses the side reaction with the electrolyte solution than the composite positive electrode active material included in the lithium battery according to Comparative Example 7.
[0282] For example, although not wishing to be bound by theory, it is understood that since the second layer formed on the surface of each of the composite positive active materials included in the lithium batteries according to Examples 5 and 6 includes Li 3 PO 4 etc., so that the wettability of the second layer to the electrolyte solution is improved, and as a result of the reaction between the second layer and the moisture, HF, etc. included in the electrolyte solution during initial charge and discharge, a stable solid electrolyte membrane is formed. As a result, additional side reactions between the composite positive electrode active material and the electrolyte solution are suppressed, and thus the surface of the composite positive electrode active material is stabilized.
[0283] In addition, since the composite positive electrode active material included in the lithium batteries according to Examples 5 and 6 has a multilayer structure including a first layer and a second layer, the life characteristics of the lithium batteries according to Examples 5 and 6 are improved compared to the composite positive electrode active material included in the lithium battery according to Comparative Example 8 and having a composite single-layer structure including the same components. In addition, although not shown in Table 3, the life characteristics of the lithium battery according to Example 8 are improved compared to the lithium battery according to Comparative Example 8.
[0284] Moreover, the lithium battery according to Example 5 has further improved life characteristics when compared with the lithium battery according to Example 8. It is believed that the improved life characteristics of the lithium battery according to Example 5 are obtained as follows: 2 ZrO 3 Not only on the surface of the core, but also in the grain boundaries of the composite positive electrode active material, each of which is located between the primary particles of the core and covers the primary particles. Therefore, the side reaction between the primary particles located inside the core and the electrolyte and the elution of the transition metal from the primary particles are suppressed, and a three-dimensional lithium ion channel is formed through the surface of the core and the second phase included in the core.
[0285] Evaluation Example 6: Evaluation of charge / discharge characteristics at high temperature
[0286] The lithium batteries prepared according to Examples 10-13 and Comparative Examples 9-12 were charged at a constant current rate of 0.1C at 45°C until the voltage reached 4.30V (relative to graphite), and then the charging process was terminated at a current rate of 0.05C while maintaining a voltage of 4.30V in a constant voltage mode. Subsequently, the lithium battery was discharged at a constant current rate of 0.1C until the voltage reached 2.8V (relative to graphite) (1st cycle, formation cycle). Gr refers to graphite.
[0287] The lithium battery undergoing the first cycle was charged at a constant current rate of 1.0C at 45°C until the voltage reached 4.30V (relative to Gr), and then the charging process was terminated at a current rate of 0.05C while maintaining a voltage of 4.30V in a constant voltage mode. Subsequently, the lithium battery was discharged at a current rate of 0.2C until the voltage reached 2.8V (relative to Gr) (second cycle).
[0288] The lithium battery undergoing the second cycle was charged at a constant current rate of 1C at 45°C until the voltage reached 4.30V (relative to Gr), and then the charging process was terminated at a current rate of 0.05C while maintaining a voltage of 4.30V in a constant voltage mode. Subsequently, the lithium battery was discharged at a current rate of 1C until the voltage reached 2.8V (relative to Gr) (the third cycle), and the cycle was repeated 300 times under the same conditions until the 302nd cycle.
[0289] The lithium battery was allowed to rest for 10 minutes after each charge / discharge cycle.
[0290] Some of the charge / discharge tests are shown in the following Table 4. The capacity retention rate at the 302nd cycle is defined as Equation 2 below.
[0291] Equation 2
[0292] Capacity retention rate [%] = [discharge capacity at the 302nd cycle / discharge capacity at the 3rd cycle] × 100%
[0293] Table 4
[0294]
[0295] As shown in Table 4, the lithium battery according to Example 10 had improved lifespan characteristics at high temperatures when compared with the lithium battery according to Comparative Example 11.
[0296] It is believed that the improvement in the life characteristics of the lithium battery according to Example 10 at high temperatures is obtained as follows: when compared with the composite positive electrode active material included in the lithium battery according to Comparative Example 11, the composite positive electrode active material included in the lithium battery of Example 10 additionally includes a second layer that further stabilizes the surface of the composite positive electrode active material.
[0297] For example, it is considered that the elution of metal ions is more effectively suppressed at high temperatures because the second layer acts as a protective layer.
[0298] Evaluation Example 7: Evaluation of charge / discharge characteristics at room temperature (Evaluation of the effect of adding 5% LFP)
[0299] The lithium battery prepared according to Examples 5 and 9 was charged at a constant current rate of 0.1C at 25°C until the voltage reached 4.30V (relative to Li), and then the charging process was terminated at a current rate of 0.05C while maintaining a voltage of 4.30V in a constant voltage mode. Subsequently, the lithium battery was discharged at a constant current rate of 0.2C until the voltage reached 2.8V (relative to Li) (1st cycle, formation cycle).
[0300] The lithium battery undergoing the first cycle was charged at a constant current rate of 0.33C at 25°C until the voltage reached 4.30V (relative to Li), and then the charging process was terminated at a current rate of 0.05C while maintaining a voltage of 4.30V in a constant voltage mode. Subsequently, the lithium battery was discharged at a current rate of 0.2C until the voltage reached 2.8V (relative to Li) (second cycle).
[0301] The lithium battery undergoing the second cycle was charged at a constant current rate of 0.33C at 25°C until the voltage reached 4.30V (relative to Li), and then the charging process was terminated at a current rate of 0.05C while maintaining a voltage of 4.30V in a constant voltage mode. Subsequently, the lithium battery was discharged at a current rate of 0.2C until the voltage reached 2.8V (relative to Li) (the third cycle).
[0302] The lithium battery undergoing the third cycle was charged at a constant current rate of 1 C at 25° C. until the voltage reached 4.30 V (relative to Li), and then the charging process was terminated at a current rate of 0.05 C while maintaining the voltage of 4.30 V in a constant voltage mode.
[0303] The discharge capacity at the 3rd cycle was used as the standard capacity.
[0304] The initial efficiency is defined as Equation 3 below.
[0305] Equation 3
[0306] Initial efficiency [%] = [discharge capacity at the first cycle / charge capacity at the first cycle] × 100%
[0307] Table 5
[0308]
[0309] As shown in Table 5, when compared with the lithium battery of Example 5, further including LiFePO 4 The lithium battery according to Example 9 has improved initial discharge capacity, initial charge / discharge efficiency, and standard capacity.
[0310] Evaluation Example 8: DC-IR evaluation at room temperature (25° C.) (evaluation with addition of 5% LFP)
[0311] The initial DC-IR of the lithium batteries prepared according to Examples 5 and 9 was measured at room temperature (25° C.) according to the following method.
[0312] In the first cycle, after charging the lithium battery to 50% state of charge (SOC) at a current rate of 0.5C,
[0313] The charging process was terminated at a current rate of 0.02C, and the lithium battery was left to stand for 10 minutes.
[0314] The lithium battery was discharged at a constant current rate of 0.5C for 30 seconds and left to stand for 30 seconds, and then the lithium battery was charged at a current rate of 0.5C for 30 seconds and left to stand for 10 seconds.
[0315] The lithium battery was discharged at a constant current rate of 1.0C for 30 seconds and left to stand for 30 seconds, and then the lithium battery was charged at a current rate of 0.5C for 1 minute and left to stand for 10 minutes.
[0316] The lithium battery was discharged at a constant current rate of 2.0C for 30 seconds and left to stand for 30 seconds, and then the lithium battery was charged at a current rate of 0.5C for 2 minutes and left to stand for 10 minutes, and
[0317] The lithium battery was discharged at a constant current rate of 3.0 C for 30 seconds and left to stand for 30 seconds, and then the lithium battery was charged at a current rate of 0.5 C for 3 minutes and left to stand for 10 minutes.
[0318] The average voltage drop over 30 seconds for each C-rate is the DC voltage value. The DC-IR is calculated based on the measured DC voltage and is shown in Table 6 below.
[0319] Table 6
[0320] Initial DC-IR[mΩ] Example 5 126 Example 9 122
[0321] As shown in Table 6, when compared with the lithium battery according to Example 5, further including LiFePO 4 The lithium battery according to Example 9 has reduced initial DC-IR.
[0322] Evaluation Example 9: Evaluation of charge / discharge characteristics at high temperature (Evaluation with addition of 5% LFP)
[0323] The lithium battery prepared according to Examples 10 and 14 was charged at a constant current rate of 0.1C at 45°C until the voltage reached 4.30V (relative to Gr), and then the charging process was cut off at a current of 0.05C while maintaining a voltage of 4.30V in a constant voltage mode. Subsequently, the lithium battery was discharged at a constant current rate of 0.1C until the voltage reached 2.8V (relative to Gr) (1st cycle, formation cycle).
[0324] The lithium battery undergoing the first cycle was charged at a constant current rate of 1.0C at 45°C until the voltage reached 4.30V (relative to Gr), and then the charging process was terminated at a current rate of 0.05C while maintaining a voltage of 4.30V in a constant voltage mode. Subsequently, the lithium battery was discharged at a current rate of 0.2C until the voltage reached 2.8V (relative to Gr) (second cycle).
[0325] The lithium battery undergoing the second cycle was charged at a constant current rate of 1C at 45°C until the voltage reached 4.30V (relative to Gr), and then the charging process was terminated at a current rate of 0.05C while maintaining a voltage of 4.30V in a constant voltage mode. Subsequently, the lithium battery was discharged at a current rate of 1C until the voltage reached 2.8V (relative to Gr) (the third cycle), and the cycle was repeated 200 times under the same conditions until the 202nd cycle.
[0326] The lithium battery was allowed to rest for 10 minutes after each charge / discharge cycle.
[0327] Some of the charge / discharge tests are shown in the following Table 7. The capacity retention rate at the 202nd cycle is defined as Equation 4 below.
[0328] Equation 4
[0329] Capacity retention rate [%] = [discharge capacity at the 202nd cycle / discharge capacity at the 3rd cycle] × 100%
[0330] Table 7
[0331] Capacity retention rate [%] Example 10 88.8 Embodiment 14 89.9
[0332] As shown in Table 7, when compared with the lithium battery according to Example 11, further including LiFePO 4 The lithium battery according to Example 14 has improved lifespan characteristics.
[0333] According to the present disclosure, the composite cathode active material includes a multi-layer coating layer in which a first layer including a first metal and a second layer including P are sequentially stacked, and thus cycle characteristics and thermal stability of a lithium battery are improved.
[0334] It should be understood that the embodiments described herein should be considered in a descriptive sense only and not for purposes of limitation. Descriptions of features or aspects within each embodiment should be considered as available for other similar features or aspects in other embodiments.
[0335] Although embodiments have been described with reference to the accompanying drawings, it will be understood by those skilled in the art that various changes in form and details may be made therein without departing from the spirit and scope as defined by the following claims.
Claims
1. Composite positive electrode active materials, include: a core comprising a plurality of primary particles; and a shell formed on the core, wherein the primary particles include a first lithium transition metal oxide including nickel, The shell includes a first layer and a second layer on the first layer, The first layer includes a first composition including a first metal, The second layer includes a second component including phosphorus, and The first metal comprises at least one of cobalt and magnesium, The core includes grain boundaries between the plurality of primary particles, and the grain boundaries include a third component including a second metal including zirconium. 2 . The composite positive electrode active material of claim 1 , wherein the first component includes a first phase, and the second component includes a second phase different from the first phase in at least one of composition and structure. 3 . The composite positive active material of claim 1 , wherein the first component includes at least one phase of: a phase having a layered crystal structure and a phase having a spinel crystal structure. 4 . The composite positive active material according to claim 3 , wherein the layered crystal structure belongs to an R-3m space group, and the spinel crystal structure belongs to an Fd-3m space group. 5 . The composite positive electrode active material of claim 1 , wherein the first layer is on a surface of a primary particle of the plurality of primary particles, and a concentration of the first metal included in the first layer is greater than a concentration of the first metal included in the plurality of primary particles. 6 . The composite positive active material of claim 1 , wherein the thickness of the second layer is greater than that of the first layer, the thickness of the first layer is 50 nanometers or less, and the thickness of the second layer is 500 nanometers or less.
7. The composite positive electrode active material according to claim 1, wherein the first component is a component including the first metal and oxygen, or a component including lithium, the first metal and oxygen, The first component include: 0 mol to 3.3 mol of lithium per 1 mol of the first component, 0.7 mol to 3.3 mol of the first metal per 1 mol of the first component, and 1.7 mol to 4.3 mol of oxygen per 1 mol of the first component.
8. The composite positive electrode active material according to claim 1, wherein the first component is represented by Formula 1: Formula 1 Li a M1 b O c in, In Formula 1, M1 is at least one of cobalt and magnesium, 0≤a≤3.1, 0.9≤b≤3.1, and 1.9≤c≤4.
1.
9. The composite cathode active material according to claim 1, wherein the first component comprises at least one of the following: Co 3 O 4 , MgO, Li where 0 < x ≤ 1.5 x CoO 2 , and Li 2 ZrO 3 .
10. The composite positive electrode active material according to claim 1, wherein the amount of the first component contained in the first layer is 10 parts by weight or less based on 100 parts by weight of the first lithium transition metal oxide, or The amount of the first metal contained in the first layer is 10 parts by weight or less based on 100 parts by weight of the first lithium transition metal oxide.
11. The composite positive electrode active material according to claim 1, wherein the second component is a component including the first metal, phosphorus and oxygen, or a component including lithium, the first metal, phosphorus and oxygen, The second component include: 0 mol to 3.3 mol of lithium per 1 mol of the second component, 0.7 mol to 3.3 mol of the first metal per 1 mol of the second component, 0.7 mol to 2.3 mol of phosphorus per 1 mol of the second component, and 3.7 mol to 8.3 mol of oxygen per 1 mol of the second component.
12. The composite positive electrode active material according to claim 1, wherein the second component is represented by the following formula 2: Formula 2 <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> a <h2 style=";text-align:left;direction:ltr"> M2<h2 style=";text-align:left;direction:ltr"> b <h2 style=";text-align:left;direction:ltr"> (PO<h2 style=";text-align:left;direction:ltr"> 4 <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> c in, In Formula 2, M2 is at least one of cobalt, magnesium, zirconium, aluminum, manganese, silicon, palladium, nickel, titanium, tin, molybdenum, iridium, platinum, ruthenium, cerium, boron, niobium, vanadium, iron and zinc, and 0≤a≤3.1, 0.9≤b≤3.1, and 0.9≤c≤2.
1.
13. The composite positive electrode active material according to claim 1, wherein the second component comprises at least one of the following: Li 3 PO 4 、LiCoPO 4 , and Co 3 (PO 4 ) 2 . 14 . The composite positive active material of claim 1 , wherein the amount of the second component or phosphorus contained in the second layer is 10 parts by weight or less based on 100 parts by weight of the first lithium transition metal oxide. 15 . The composite positive active material of claim 1 , wherein the third component comprises a third phase having a monoclinic crystal structure, and the monoclinic crystal structure belongs to a C2 / m, C12 / c1, or C2 / c space group.
16. The composite positive active material of claim 1, wherein the second metal further comprises at least one of aluminum, cobalt, magnesium, manganese, silicon, molybdenum, palladium, titanium, tin, iridium, platinum, ruthenium, cerium, boron, niobium, vanadium, iron and zinc.
17. The composite positive electrode active material according to claim 1, wherein the third component comprises lithium, the second metal, and oxygen, and wherein the third component include: 1.7 mol to 2.3 mol of lithium per 1 mol of the third component, 0.7 mol to 1.3 mol of the second metal per 1 mol of the third component, and 2.7 mol to 3.3 mol of oxygen per 1 mol of the third component.
18. The composite positive electrode active material according to claim 1, wherein the third component is represented by the following formula 3: Formula 3 Read a M3 b Oh c in, In Formula 3, M3 is at least one of zirconium, aluminum, cobalt, magnesium, manganese, silicon, palladium, nickel, titanium, tin, iridium, platinum and ruthenium, 1.9≤a≤2.1, 0.9≤b≤1.1, and 2.9≤a≤3.
1.
19. The composite positive active material of claim 1, wherein the shell further comprises the third component. 20 . The composite cathode active material of claim 1 , wherein the first lithium transition metal oxide comprises a second metal.
21. The composite positive electrode active material according to claim 1, wherein the first lithium transition metal oxide comprises lithium, nickel, a second metal, a third metal and oxygen, wherein the first lithium transition metal oxide include: 0.1 mol to 1.3 mol of lithium per 1 mol of the first lithium transition metal oxide, 0.7 mol to 0.99 mol of nickel per 1 mol of the first lithium transition metal oxide, 0.001 mol to 0.01 mol of the second metal per 1 mol of the first lithium transition metal oxide, 0.01 mol to 0.3 mol of the third metal per 1 mol of the first lithium transition metal oxide, and 1.7 to 2.3 moles of oxygen per 1 mole of the first lithium transition metal oxide, and wherein the third metal is a metal other than lithium, nickel, and the second metal.
22. The composite cathode active material according to claim 1, wherein the first lithium transition metal oxide is represented by Formula 4: Formula 4 Li a M4O 2-α X α Wherein, in Formula 4, 0.9 ≤ a ≤ 1.1 and 0 ≤ α < 2, M4 is nickel, the second metal, and the third metal, wherein the third metal includes at least one element of Groups 2 to 13 of the periodic table other than nickel and the second metal, and the amount of nickel contained in M4 is 70 mol% or more, based on the total amount of M4, and X is at least one of fluorine, sulfur, and phosphorus.
23. The composite cathode active material according to claim 1, wherein the first lithium transition metal oxide is represented by Formula 5: Formula 5 Li a Ni b M5 c M6 d M7 e O 2-α X α Wherein, in Formula 5, 0.9 ≤ a ≤ 1.1, 0.7 < b < 1.0, 0 < c < 0.3, 0 < d < 0.3, 0 ≤ e < 0.1, b + c + d + e = 1, and 0 ≤ α < 2, M5, M6, and M7 are different from each other and are each independently cobalt, manganese, zirconium, aluminum, rhenium, vanadium, chromium, iron, boron, ruthenium, titanium, niobium, molybdenum, magnesium, and platinum, and X is at least one of fluorine, sulfur, and phosphorus.
24. The composite cathode active material according to claim 1, wherein the first lithium transition metal oxide is represented by at least one of Formula 6 and Formula 7: Formula 6 Li a Ni b Co c Mn d M8 e O 2-α X α and Formula 7 Li a Ni b Co c Al d M8 e O 2-α X α Wherein, in Formulas 6 and 7, a, b, c, d, e, and α are each independently 0.9 ≤ a ≤ 1.1, 0.7 < b < 1.0, 0 < c < 0.1, 0 < d < 0.1, 0 ≤ e < 0.01, b + c + d + e = 1, and 0 ≤ α < 2, M8 is at least one of zirconium, aluminum, vanadium, chromium, iron, rhenium, boron, ruthenium, titanium, niobium, molybdenum, magnesium, and platinum, and X is at least one of fluorine, sulfur, and phosphorus.
25. The composite cathode active material according to claim 1, wherein the first lithium transition metal oxide is represented by Formula 8: Formula 8 aLi 2 MnO 3 ·(1-a)LiMO 2-α X α Wherein, in Formula 8, 0 < a < 1 and 0 ≤ α < 2, M is at least two elements of nickel, cobalt, manganese, zirconium, aluminum, rhenium, vanadium, chromium, iron, boron, ruthenium, titanium, niobium, molybdenum, magnesium, and platinum, and M includes at least Ni, and X is at least one of fluorine, sulfur, and phosphorus.
26. A cathode comprising the composite cathode active material according to any one of claims 1 - 25.
27. The cathode according to claim 26, wherein the cathode further comprises a cathode active material having an olivine structure.
28. The cathode according to claim 27, wherein the amount of the cathode active material having an olivine structure is 10 wt% or less, based on the total weight of the cathode active material.
29. A lithium battery, comprising: a cathode according to any one of claims 26 - 28; an anode; and an electrolyte between the cathode and the anode.
30. A method for preparing the composite cathode active material according to any one of claims 1 - 25, the method comprising: providing a first lithium transition metal oxide; mixing the first lithium transition metal oxide with a first metal precursor to prepare a first composition; mixing the first composition with a phosphorus precursor to prepare a second composition; drying the second composition; as well as The dried second composition is heat-treated at a temperature of 400° C. to 1000° C. in an oxidizing atmosphere to prepare the composite positive active material.
31. The method of claim 30, wherein providing a first lithium transition metal oxide include: mixing a precursor of the first lithium transition metal oxide and a second metal precursor to prepare a mixture; as well as The mixture is heat-treated at a temperature of 400° C. to 1000° C. in an oxidizing atmosphere to provide the first lithium transition metal oxide.
